Giant strain with low hysteresis in A-site-deficient (Bi0.5Na0.5)TiO3-based lead-free piezoceramics. (15th April 2017) - Li, Tangyuan; Lou, Xiaojie; Ke, Xiaoqin; Cheng, Shaodong; Mi, Shaobo; Wang, Xiangjian; Shi, Jing; Liu, Xiao; Dong, Guangzhi; Fan, Huiqing; Wang, Yunzhi; Tan, Xiaoli
Abstract: We report a giant strain (0.72%) with a low degree of hysteresis ( ca . 36.2%) and a giant S max / E max ratio (916 pm V −1, S max and E max denote the maximum strain and the corresponding electric field, respectively) for lead-free (1− x )(0.8Bi0.5 Na0.5 TiO3 -0.2Bi0.5 K0.5 TiO3 )- x Sr0.8 Bi0.1 □0.1 Ti0.8 Zr0.2 O2.95 piezoceramics with x  = 0.06. The giant strain originates from a reversible transition between the ergodic relaxor and ferroelectric states under applied electric fields. A-site vacancies (VA ) and oxygen vacancies (VO ), deliberately introduced to the system, induce a randomly distributed local polarization field. The local field induces embryonic polarization domains that have a broad distribution of maturity and thus smears the transition between the ferroelectric and relaxor states. This leads to a narrow hysteresis loop. The poling field required for the relaxor-to-ferroelectric transition is reduced significantly, due to the remanent ferroelectric phase at zero field acting as the seed, and the point defects synergistically facilitating the nucleation and growth of the ferroelectric phase. Our work provides a novel route for designing piezoelectric materials with both a giant strain and a narrow hysteresis for practical actuator applications. Graphical abstract: Image 1